Pengaruh Risiko Kredit, Kecukupan Modal, dan Likuiditas terhadap Profitabilitas Bank Konvensional yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2024 - Ranti Amelia Suardi; Saparuddin M; Herlitah Herlitah (Indo Publishing, 2026)
This study analyzes the effect of credit risk (NPL), capital adequacy (CAR), and liquidity (LDR) on profitability (ROA) of conventional banks listed on the Indonesia Stock Exchange for the 2019-2024 period. Using a quantitative approach with panel data regression and Random Effect Model, the sample consists of 33 banks with 198 observations. The results show that NPL has a negative and significant effect on ROA with a coefficient of -0.328903 (p-value 0.0000), indicating that increased non-performing loans force banks to raise loan loss provisions, ultimately reducing net income. CAR shows a positive but insignificant effect with a coefficient of 0.005816 (p-value 0.3843), suggesting that maintaining a high capital buffer does not automatically improve profitability if capital is not deployed productively. Similarly, LDR shows a positive but insignificant effect with a coefficient of 0.008889 (p-value 0.0820), implying that aggressive lending without adequate credit quality may not yield expected profit improvement. Simultaneously, NPL, CAR, and LDR significantly affect ROA with F-statistic probability of 0.000000. The R² of 0.191442 indicates that the three variables explain 19.14% of profitability variation, while the remaining 80.86% is explained by other factors outside the model.